THE IMPACT OF ONLINE COSTUMER REVIEW AND CELEBRITY ENDORSEMENT ON PURCHASE INTENTION (Case Study of Nanospray MCI Indonesia) - Sondakh, Lavenia.J. (Sam Ratulangi University, 2016)
Facial treatments become one of the important roles to maximize appearance. In recent years comes tool for skin care, namely Nanospray of MCI Indonesia. A care tools that became very popular in the society. Many customers buy a product and then give a review of the benefits obtained from the product. There were also many the celebrities advertise these products. The purpose of this study was to find out the influence of online customer reviews and celebrity endorsements to the customers purchase intention on Nanospray MCI Indonesia. The method used to analyze the data is Multiple Regression Analysis. The population observed is consumers who ever bought a product of Nanospray MCI Indonesia in Manado, North Sulawesi with sample size ofÂ 100 respondents. The results of this research showed a significant influence of online customer reviews and celebrity endorsements to the customer's purchase intention simultaneously. Recommendations the researcher suggest to paying attention on Celebrity endorsement, because Celebrity endorsement has a strong effect on consumer memory and learning approach too. Likewise with online customer review also suggested that the marketers should give a good perception and motivation for consumers to understand the products offered.